SISTEM PENDIDIKAN FORMAL DI PONDOK PESANTREN (Studi pada Pondok Pesantren Babul Hikmah Kecamatan Kalianda Kabupaten Lampung Selatan) - Inayah, Nur; Fatimaningsih, Endry (SOCIOLOGIE, 2013)
This research is intended to explain the system of formal education in Pondok Pesantren Babul Hikmah Kecamatan Kalianda Kabupaten Lampung Selatan which includes education curriculum and methods of instruction applied in the process of learning. Type of research used in this research is qualitative with a method of collecting data observation and interview depth. Technical data analysis conducted by ways reduction of data, display data, and conclusion. From the research showed that Pondok Pesantren Babul Hikmah the lesson from implemented the system of formal education that is divided at the level of MI, MTs, and SMAIT. Education curriculum applied namely: curriculum national education, curriculumÂ  the ministry of religion, and curriculum pesantren. The reason the implementation of the curriculum in the region to meet the needs of people are going to the science of religion and science of general. The application of this integrated curriculum is implemented in classes at the formal school. Curriculum Diknas, Depag or pesantren having rations number of hours learn the same in school formal, exception when is outside school hours formal there are extra hours specifically to curriculum pesantren. An impediment in the implementation of this script low-self quality and quantity of human resources for teachers, the lack of a facility education, and the absence of selection for a candidate santri, so that an impact on the level of seriousness santri in learning. The method of learning that applied is: a method of lectures, a method of rote, methods of discussion, and methods of the assignment as well as program bashul kitab. Bashul kitab is the program evaluation shaped scientific work to dissect kitab in order to assess the ability and understanding santri against learning. An impediment in the learning process of learning, namely a lack of facilities santri, the condition that is not conducive and absence teacher in the process of learning.Keywords:Â Education system, pondok pesantren